The strong influence of small construction errors on sound insulation of buildings with heavyweight concrete structure: A Portuguese case study. Issue 2 (June 2023) - Mateus, Diogo; Pereira, Andreia
In order to attain an expected sound insulation in buildings, it is necessary to employ appropriated constructive solutions, but it is also fundamental to guarantee compatibility with other involved design professional fields, proper detailing of solutions and correct on site mounting. A solution with a predicted high acoustic performance may result in failure if there is no proper interconnection between other design professional areas or if execution mistakes occur, even if of very small dimension. The main objective of this technical paper is to analyse the influence of defects that typically occur in buildings, located in Portugal, resulting in very poor airborne or impact sound insulation performance. The chosen situations refer to buildings with heavyweight concrete structure, where small construction defects occurred and/or wrong decisions were taken, ending up with a large reduction on the final acoustic performance. Some of these errors, given their small size or because they occurred in hidden zones, easily passed unnoticed, on site. The defects here addressed in what refers to airborne sound insulation are related with execution of double masonry hollow brick walls, sound bridges in acoustic suspended ceilings, passage of ventilation or sewage pipes, inappropriate installation of acoustic doors, shutter boxes or windows. As for impact sound insulation, the presence of rigid connections is the main focus of the characterisation here performed.